Implementasi Peraturan Daerah Nomor 4 Tahun 2022 tentang Pelestarian dan Pengelolaan Cagar Budaya oleh Dinas Kebudayaan dan Pariwisata Kota Tanjungpinang - Amiliya Febriani; Junriana Junriana (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
This study aims to analyze the implementation of Tanjungpinang City Regional Regulation Number 4 of 2022 concerning the Preservation and Management of Cultural Heritage by the Department of Culture and Tourism of Tanjungpinang City. This research was motivated by various problems encountered in the preservation and management of cultural heritage, including limited human resources, budget constraints, suboptimal coordination among related institutions, and low public participation in supporting cultural heritage preservation in Tanjungpinang City. This study employed a qualitative research method with a descriptive approach. Data were collected through observation and interviews. Informants were selected using a purposive sampling technique and consisted of officials from the Department of Culture and Tourism of Tanjungpinang City, the Department of Culture of Riau Islands Province, the Cultural Preservation Center Region IV, the Cultural Heritage Expert Team (TACB), cultural heritage caretakers, village officials, traditional leaders, community leaders, and local communities surrounding cultural heritage sites. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. This study applied the policy implementation theory of Van Meter and Van Horn, consisting of policy standards and objectives, resources, characteristics of implementing organizations, inter-organizational communication and implementation activities, implementers disposition, and the social and economic environment. The results of the study indicate that the implementation of Tanjungpinang City Regional Regulation Number 4 of 2022 concerning the Preservation and Management of Cultural Heritage has been carried out by the Department of Culture and Tourism of Tanjungpinang City however it has not yet been fully optimal. In terms of policy standards and objectives, the policy goals have been well understood by the implementers. Regarding resources, limitations in expert personnel and budget support remain significant challenges. The characteristics of the implementing organization demonstrate a clear division of tasks, although inter-agency coordination still needs improvement. Inter-organizational communication has been conducted through various coordination mechanisms, but it has not operated optimally. The implementers have shown a strong commitment to supporting cultural heritage preservation. Meanwhile the social and economic environment reflects community support, although the level of public participation remains uneven. Therefore, it is necessary to strengthen resource capacity, enhance coordination among stakeholders, and increase public participation to support the sustainable preservation and management of cultural heritage in Tanjungpinang City.